Cause & effect - Ackert, Patricia (Heinle and Heinle, 1994)
This book offers challenging and entertaining readings of gradually increasing length and complexity, presented within a carefully controlled system of vocabulary. New to the second edition: prereading activities new readings on new topics, and postreading writing exercises